PkM Pelatihan Penyusunan Laporan Keuangan pada BumMas Kresja Sebagai Peningkatan Pengelolaan Usaha Terdampak Pandemi - Malesa Anan (Sekolah Tinggi Ekonomi Bisnis Syariah Bina Mandiri, 2023)
BUMMAS (Community Owned Enterprise) KRESJA is one of the Community Owned Enterprises located in Firdaus village, Sei Rampah District, and Deli Serdang Regency, which consists of various business units from at least 43,825 business units in the Sei Rampah area that are engaged in the business of processing snacks or ole-ole typical of the area. From the results of interviews with BUMMAS KRESJA management during the PkM pre-activity survey, information was obtained that there were still many MSME entrepreneurs who had not kept financial records of the business units they were running. This is caused by the absence of human resources who can prepare financial reports, especially those that are in accordance with the basic principles of accounting. This community service activity (PkM) is independent in nature and carried out by Dharmawangsa University lecturers. In its implementation, it is carried out using two methods, namely the lecture method (socialization) and the tutor method (practice). Based on the activities that have been carried out by the lecturer in implementing the PkM community service activities for activity partners, namely the MSME actors group who are members of BUMMAS KRESJA, it can be concluded that the activities are going as expected. This is due to participants and partners who are enthusiastic about participating in a series of activities. Communication was also established during the activities carried out, with question-and-answer discussions related to accounting and the preparation of activity reports. From this activity, it is hoped that it will provide benefits to partners in the form of independence, ability, and skills in compiling financial reports for MSME business units that are members of BUMMAS KRESJA.